LEGAL AND POLICY FORMULATION FOR COMMUNITY POLICING IN CURBING CRIME IN NIGERIA - Ekpenisi, Collins; Aidonojie, Paul Atagamen; Okonji, Ifesinachi Charles; Okpoko, Mercy; Eregbuonye, Obieshi (Universitas Syiah Kuala, 2025)
Given the rise of community policing, crime prevention and control strategies have become similar across different jurisdictions. However, in Nigeria, effective community policing has yet to be realized due to the absence of a comprehensive legal and policy framework. This study examines the legal and policy mechanisms necessary to institutionalize community policing as a tool for reducing crime in Nigeria, comparing them with best practices from other countries and global standards. It addresses key issues such as an ineffective policing system, mistrust between the police and the public, inadequate legal structures, and inconsistent policy directives. The study proposes a structured legal and policy framework to strengthen community policing and enhance public safety. Employing a doctrinal research approach, the study critically analyzes relevant laws, policies, and international best practices, supplemented by empirical data from selected Nigerian communities. It also offers a comparative evaluation of countries with varying levels of community policing success, drawing valuable insights. The research identifies significant gaps in legal partnerships and coordination, as well as diminished community ownership resulting from distrust and lack of transparency. Consequently, establishing a strong legal and policy foundation is crucial for formalizing and operationalizing community policing in Nigeria. The study recommends enacting a comprehensive Community Policing Act, enhancing stakeholder capacity, and fostering civic engagement to build mutual trust and cooperation between law enforcement agencies and local communities.